Role of judgment in promoting nurses' decisions and ethical behavior - Fariba Borhani; Abbas Abbaszadeh; Abbas Bahrampour; Golnaz Forough Ameri; Azita Aryaeenezhad (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: Ethical decision-making and behavior of nurses are major factors, which can effect on the quality of nursing care. It seems that there is a correlation between demographic variables and ethical decision-making and moral behaviors of nurses. Promoting patients' health is one of the issues related to nurses' ethical behaviors. The aim of this study was to determine the role of judgment in promoting nurses' decisions and ethical behavior. MATERIALS AND METHODS: This was a descriptive, cross-sectional study in which 260 nurses were selected based on the inclusion criteria. Sampling method was available. The data collection tool was the Hospital Ethics Committee Survey Questionnaire. Data were analyzed by SPSS software version 20. RESULTS: In this study, judgments and ethical behaviors of nurses were evaluated at the moderate and good level. Gender, marriage status, education level, and nursing position were effective in judgments and ethical behavior of nurses. Age, job experience, and participation in the ethics workshop had no significant effect on ethical behavior and moral judgment. The mean score of moral belief of nurses participating in this study was 181.56 ± 17.60, and their mean moral practice in the real environment was 168.5 ± 17.77. CONCLUSION: The judgment competencies in ethical situation of nurses should be promoted to a higher level. It seems that more advanced educational methods are needed to achieve this goal. The findings from this study show the necessity of nurses' ability to improve their behavior and moral judgment. It also shows that nurses need more reinforcement based on the demographic variables.